The Effect of Squat Training on Long Jump Ability - Sulasikin Sahdi Kadir; Gilang Ramadan; Arief Ibnu Haryanto; Giofandi Samin; Iwan Fataha; Ardin Abdul Gani (JUARA : Jurnal Olahraga, 2021)
The purpose of this study was to determine the effect of squat training on long jump abilities. The research method used was one group pre-test and post-test. This study consisted of 20 students of class XI Computer Network Engineering who were taken randomly. Research results in peer squat exercise, which affects students' long jump abilities, have been studied before. Still, the difference with this study is that the method used is peer squat exercise, which is done in pairs to provide a new atmosphere and make students not feel bored. This study concludes that peer squat exercise, which is done in pairs, positively affects the long jump ability in athletic sports.